2016
DOI: 10.1128/mcb.00182-16
|View full text |Cite
|
Sign up to set email alerts
|

Function of Conserved Topological Regions within the Saccharomyces cerevisiae Basal Transcription Factor TFIIH

Abstract: bTFIIH is a 10-subunit RNA polymerase II basal transcription factor with a dual role in DNA repair. TFIIH contains three enzymatic functions and over 30 conserved subdomains and topological regions. We systematically tested the function of these regions in three TFIIH core module subunits, i.e., Ssl1, Tfb4, and Tfb2, in the DNA translocase subunit Ssl2, and in the kinase module subunit Tfb3. Our results are consistent with previously predicted roles for the Tfb2 Hub, Ssl2 Lock, and Tfb3 Latch regions, with mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
4
15
1
Order By: Relevance
“…Combined with secondary structure prediction showing a very long α-helix in MAT1 (Extended Data Fig. 4) and CX-MS and site-specific crosslinking data showing proximity of MAT1 to XPB and XPD 7,29 (Fig. 3c, d), these observations strongly support our assignment of MAT1.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Combined with secondary structure prediction showing a very long α-helix in MAT1 (Extended Data Fig. 4) and CX-MS and site-specific crosslinking data showing proximity of MAT1 to XPB and XPD 7,29 (Fig. 3c, d), these observations strongly support our assignment of MAT1.…”
supporting
confidence: 85%
“…Mutations of C259 (partly occluded yellow sphere) impair the MAT1–XPD interaction. Site-specific crosslinks (SS) between RAD3 and TFB3 (yeast homologues of XPD and MAT1) 29 shown as purple spheres, CX-MS crosslinks (CX; same as in c ) light orange. Unassigned density that may correspond to the N-terminal RING domain of MAT1 (Extended Data Fig.…”
Section: Figurementioning
confidence: 99%
“…Consequently, the deletion of the C-terminal p34 domain affects both the stability of human TFIIH and its NER and transcription activities (Figure 4E and F ). Intriguingly, yeast genetics demonstrated that the deletion of the C4 domain was lethal ( 10 ). How the C-terminal domain of p34 exactly interacts with other TFIIH partners requires further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…15 residues of p44 span the 175 distance between the p44 vWFA domain and the XPB NTD, where a small helical 176 motif in p44 contacts XPB residues 72-75, 95-102, and 139-143, in agreement 177 with CX-MS data (Luo et al, 2015) (Figure 1 -figure supplement 6E). Partial 178 deletion of the p44 NTE in yeast causes a slow-growth phenotype, suggesting a 179 functional role for this p44-XPB interaction (Warfield et al, 2016). The XPB NTD is the site of the two human disease mutations F99S and T119P, 302 which cause XP and TTD, respectively (Cleaver et al, 1999).…”
Section: Introduction 36 37mentioning
confidence: 99%